All in the family : the Trumps and how we got this way [compact disc, unabridged] - Trump, Fred C. (Frederick Crist), III, 1962- (Simon & Schuster Audio, 2024)
Fred C. Trump III, nephew of President Donald Trump, breaks his decades-long silence in this honest memoir and sheds a whole new light on the family name.